2020
DOI: 10.1021/acs.organomet.0c00418
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Limits of Oxidative Addition of C(sp3)–X Bonds toward Selected N,C,N-Chelated Bismuth(I) Compounds

Abstract: The reactivity of two N,C,N-chelated bismuthinidenes, that is, [2, 2 C 6 H 3 ]Bi (1) and its metastable analogue [2,6-(Me 2 NCH 2 ) 2 C 6 H 3 ]Bi (2), toward organic substrates containing C(sp 3 )−X bond (where X = I or OTf) is reported. The aim of this study is to prove the potential of the Bi(I) center in 1 and 2 to participate in an oxidative addition toward C−X bonds under formation of corresponding trivalent bismuth compounds. The influence of the substrate is examined; thus, simple primary alkyls (includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…The Bi I /Bi III couple has been much less studied in the context of organo­pnicto­gen chemistry, as only recently have discrete redox events in this manifold been explored. Of particular note is the seminal work of Dostál, who has demonstrated that Lewis base-stabilized aryl-Bi­(III) dihydrides undergo facile release of H 2 to generate the corresponding aryl-Bi­(I) compounds, , which are then amenable to oxidative addition to deliver Bi­(III) species. Bismuth­(III) alkoxides also undergo Bi–O homolysis in certain cases, , a potentially relevant step in the SOHIO ammoxidation process for the synthesis of acrylonitrile from propylene. These rare examples represent the early stages of accessing low-valent organobismuth centers to enable redox events and have begun to find application in catalysis.…”
Section: State-of-the-art Developments In Organopnictogen Redox Catal...mentioning
confidence: 99%
“…The Bi I /Bi III couple has been much less studied in the context of organo­pnicto­gen chemistry, as only recently have discrete redox events in this manifold been explored. Of particular note is the seminal work of Dostál, who has demonstrated that Lewis base-stabilized aryl-Bi­(III) dihydrides undergo facile release of H 2 to generate the corresponding aryl-Bi­(I) compounds, , which are then amenable to oxidative addition to deliver Bi­(III) species. Bismuth­(III) alkoxides also undergo Bi–O homolysis in certain cases, , a potentially relevant step in the SOHIO ammoxidation process for the synthesis of acrylonitrile from propylene. These rare examples represent the early stages of accessing low-valent organobismuth centers to enable redox events and have begun to find application in catalysis.…”
Section: State-of-the-art Developments In Organopnictogen Redox Catal...mentioning
confidence: 99%
“…The X-ray crystal structure of 8b confirms the weak interaction between the cationic Bi center and the triflate anion, as shown by the large distance between the closest oxygens of triflate and the Bi center (2.974 Å, ∑ cov (Bi–O) = 2.14 Å, Figure B). In spite of the cationic nature of 8b , the Bi1–C4 bond is still polarized [2.294(2) Å] . As a result, 8b is highly moisture-sensitive, yielding [Phebox-Bi­(OTf)] 2 O, 2b , and other oxo-bismuth species upon hydrolysis .…”
mentioning
confidence: 99%
“…As a result of the high nucleophilicity of the 6p 2 lone pair on the Bi(I) center, bismuthinidene 1 has recently been shown to engage in polar SN2-type reactions with alkyl halides and triflates. 36 Similarly, 1 reacted quantitatively with a range of benzyl (pseudo)halides (Cl, Br, I, OMs) to give benzyl bismuth(III) complexes 5-8 (Fig. 2b).…”
Section: Resultsmentioning
confidence: 99%
“…In order to compete favorably with TCPhth, synthetically relevant N-heterocycles bearing free N-H bonds were evaluated. Using proline-derived RAE 22, the corresponding C-N coupling products with a variety of benzimidazoles (26,40), imidazoles (33, 39, 41), and pyrazoles (31,32,(35)(36)(37)(38) were obtained. Non-symmetrical heterocycles such as benzotriazole (34) could also be accommodated, providing the product in a 5:1 N1/N2 ratio of regioisomers.…”
Section: Resultsmentioning
confidence: 99%